Process mineralogy approach to optimize curing-leaching in vanadium-bearing stone coal processing plants - Hui Li; Yuexin Han; Jianping Jin; Peng Gao; Zhenya Zhou (International Journal of Mining Science and Technology, 2023)
The purpose of this study is to apply process mineralogy as a practical tool to further understand and analyze the reasons for low leaching rates in the curing-leaching process of vanadium-bearing stone coal and to find a solution or improvement to optimize the leaching index. Using vanadium-bearing stone coal with the V2O5 mass fraction of 0.88% as the research object, the effects of particle size, mineral composition, and sulfuric acid curing on the feed, intermediate, and final products of curing-leaching were analyzed. The main vanadium-bearing minerals in the feed samples included sericite/illite, montmorillonite, kaolinite, limonite, and schreyerite. Through the penetration depth analysis of sulfuric acid, the reason for the high vanadium content in the coarse leaching residue (0.205% V2O5) was found, mainly due to the poor curing effect and incomplete washing after screening. Therefore, thorough washing after sieving and further optimizing the curing process are necessary. The vanadium content of the fine leaching residue (0.078%) was low and the curing-leaching effect was good. However, the vanadium content in the thickened residue (0.296%) exceeded that in the fine leaching residue, which was attributed to the neutralization reaction in the #1 thickener. To solve this problem, the neutralization and thickening processes should be performed in separate equipment. The analysis and detection of key products is helpful for identifying problems and improving the curing-leaching circuit process.